Determinants of the Productivity Change for the Banking Sector in Egypt. Issue 2 (April 2018) - Jreisat, Ammar; Hassan, Hassan; Shankar, Sriram
This study aims to undertake an evaluation and examination of the productivity change of the Egyptian banking sector, using a novel data set which covers 14 banks operating in the Egyptian market from 1997 to 2013. We use a non-parametric approach Data Envelopment Analysis (DEA) based analysis to investigate the productivity change in the Egyptian banking sector. Input-oriented Malmquist indices of productivity change are estimated with DEA to measure total factor productivity (TFP) change. The TFP changes are decomposed into the product of technological change and technical efficiency change (catch up). In the second stage, potential determinants of productivity change are studied using a regression model. We find that the Egyptian banking sector as a whole shows a productivity regress of 0.9 per cent per year, which is mainly due to the technological improvements. The estimated regression model identifies some variables which significantly influence the productivity of banks in Egypt. The banks with higher loans to deposit ratio and higher returns on equity have higher productivity growth reflecting on their strong strategic and managerial skills. The size of bank seems to be associated with an increase in productivity. The maturity of a bank (measured by age) is associated with higher productivity. The net interest margin (NIM) and non-interest expense over total assets (NIETA) variables do not seem to be affecting the productivity of banks. Surprisingly, our results reveal that the financial crisis is negatively and statistically insignificant which means there are no effects on the Egyptian banks.